Cybersecurity essentials - Brooks, Charles J.; Grow, Christopher; Craig, Philip; Short, Donald (Sybex, 2017)
An accessible introduction to cybersecurity concepts and practices, 'Cybersecurity Essentials' provides a comprehensive introduction to the field, with expert coverage of essential topics required for entry-level cybersecurity certifications.